Analysis Of Investment, Foreign Investment, Workforce, And Exchange Rate Influence For Economic Growth In North Sumatera. Issue 8 (2019) - , Yasmurni Zebua; , Muhammad Fitri Rahmadana; Nasir, Muhammad
No abstract available